Successful Delayed Neurolysis of the Median Nerve in a Teenager 7 years After Supracondylar Fracture: A Case Report and Review of the Literature. Issue 4 (October 2021) - Choong, Jia; Baldrighi, Carla; Oestreitch, Kerstin; Jester, Andrea
Abstract: Supracondylar humeral fractures are the commonest elbow fractures in childhood, associated with a high rate of neurological complications. We present the case of a 14-year-old adolescent girl with persisting daily pain, lack of sensation, and strength to her left hand after a displaced supracondylar fracture 7 years earlier. At the time of the fracture, she underwent closed reduction and percutaneous Kirschner wire fixation. During revision surgery, half of the median nerve was found embedded in bone at the level consistent with the healed fracture site. Neurolysis of the fascicles adherent to the bone was performed. Postoperatively, the patient had complete recovery of sensation, reduced pain, and a 2.5-fold improvement of grip strength. This case shows that there is a role for delayed neurolysis in children.